Effects of Rootstocks on Blade Nutritional Content of Two Minority Grapevine Varieties Cultivated under Hyper-Arid Conditions in Northern Chile - Nicolás Verdugo-Vásquez; Gastón Gutiérrez-Gamboa; Emilio Villalobos-Soublett; Andrés Zurita-Silva (Agronomy, 2021)
In the 90s, as in other countries, transformation of Chilean viticulture brought about the introduction and spread of European grapevine varieties which has resulted in a massive loss of minor local and autochthonous grapevine varieties traditionally grown in several wine growing regions. Fortunately, in recent years, autochthonous and minority varieties have been revalued due to their high tolerance to pests and diseases and because of their adaptation to thermal and water stress triggered by global warming. In this study, we assessed the nutritional status of two autochthonous grapevines grafted onto four different rootstocks under the hyper-arid climatic conditions of Northern Chile over three consecutive seasons. The results showed that R32 rootstock induced high N, P, Ca, Mg and Mn levels in blades compared to Harmony rootstock. R32 rootstock and to a lesser extent, 1103 Paulsen and 140 Ruggeri rootstocks kept balanced levels of nutrients in blades collected from Moscatel Amarilla and Moscatel Negra grapevine varieties. Additionally, Harmony presented slight nutritional imbalance compared to the rest of studied rootstocks due to its low absorption of Mg, Mn, Ca and P, and its high K absorption, which was exacerbated under warm weather and salinity soil conditions. These results may provide a basis for specific cultivar/rootstock/site combinations, a nutritional guide for the viticulturists of Northern Chile, and options to diversify their production favoring the use of minority and autochthonous varieties that adapt well to hyper-arid conditions of Northern Chile.